Older Adult Learners’ Willingness to Communicate in English during Task Performance - Anna Borkowska (Acta Universitatis Wratislaviensis. Anglica Wratislaviensia)
The article primarily intends to explore older adults’ willingness to communicate (WTC) during dyadic work, as well as to identify communication strategies (CSs) applied in the course of task performance. The instrument comprised biodata items, In-Class WTC Level Scale, and In-Class WTC Self-Assessment Scale. The data analysis revealed that the older adult learners (sixteen students) were eager to communicate in English in class during an information-gap activity. The task type seemed to exert a positive influence on their WTC, and they appreciated the role of the interlocutor. The results also showed a strong positive correlation between in-class WTC level and the duration of learning English indicating that the older adults’ WTC enhanced as the length of learning English increased. The participants employed mainly direct strategies, namely retrieval, self-repair, and self-paraphrasing. Retrieval was the most commonly used as it helped to gain time to express thoughts effectively. When it comes to interactional strategies, the age-advanced learners applied repetition requests and confirmation which suggested the partner played a vital role in achieving a communicative goal.